Socio-Cognitive Factors Associated With Lifestyle Changes in Response to the COVID-19 Epidemic in the General Population: Results From a Cross-Sectional Study in France - Constant, Aymery; Conserve, Donaldson Fadael; Gallopel-Morvan, Karine; Raude, Jocelyn (Frontiers in Psychology, 2020)
Background: The aims of the present study were to assess changes in lifestyles in the general population in response to coronavirus disease 2019 (COVID-19) lockdown and the influence of COVID-19 perceptions, as assessed by the Extended Parallel Process Model (EPPM), on these changes. Methods: Data were collected from 4005 individuals through an online survey conducted 3 to 4 weeks after the nationwide lockdown implementation in France. Participants were asked whether they practiced five behaviours (i.e.: screen watching, snacking, eating fruits and vegetables, exercising, and walking) less often, as often as, or more often than prior to the lockdown. Beliefs and expectations towards the COVID-19 epidemic were also assessed using an adapted version of EPPM, together with sociodemographic and environmental variables. Results: More than 8 in 10 respondents reported unhealthy changes in lifestyle since the lockdown, mostly in relation to physical activity. The unhealthy changes were positively associated with male sex (Rate ratio (RR) = 1.17; Confidence Interval [95% CI] = 1.10 – 1.24), living urban density, having garden (RR=1.16 [1.07 – 1.26]), financial difficulties because of COVID-19 (RR=1.09 [1.02 – 1.18]), lack of fear control (RR=1.04 [1.01 – 1.09]), and negatively with cognitive avoidance (RR=0.92 [0.89 – 0.95]). Less than 4 in 10 respondents reported healthy changes, mostly in relation to better eating habits. They were positively associated with living with more than two persons (RR=1.22 [1.02-1.45]), having a terrace (RR=1.14 [1.02 – 1.29], perceived efficacy (RR=1.11 [1.04 – 1.08]) and negatively with being aged 40 or higher. Alcohol consumption overall declined in regular drinkers, while a slight increase in tobacco use was observed in regular smokers, Discussion: The COVID-19 pandemic and lockdown resulted in frequent and mostly unhealthy changes in lifestyle among in the general population. They were related to individual and environmental characteristics, but also to EPPM appraisals in the in the wake of fear appeal from COVID-19 campaigns. Communication and preventive measures should include messages and initiatives towards the maintenance of healthy lifestyles during pandemics such as the adaptation of physical activity and eating guidelines to the particular contexts of mobility restriction and infection control.